2020
DOI: 10.1038/s41416-020-01180-1
|View full text |Cite
|
Sign up to set email alerts
|

A Phase 1 study of RO6870810, a novel bromodomain and extra-terminal protein inhibitor, in patients with NUT carcinoma, other solid tumours, or diffuse large B-cell lymphoma

Abstract: Background Bromodomain and extra-terminal (BET) proteins are epigenetic readers that can drive carcinogenesis and therapy resistance. RO6870810 is a novel, small-molecule BET inhibitor. Methods We conducted a Phase 1 study of RO6870810 administered subcutaneously for 21 or 14 days of 28- or 21-day cycles, respectively, in patients with the nuclear protein of the testis carcinoma (NC), other solid tumours, or diffuse large B-cell lymphoma (DLBCL) with MYC d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(60 citation statements)
references
References 50 publications
(36 reference statements)
3
57
0
Order By: Relevance
“…While our pharmacodynamic findings provided evidence for on-target effects of RO6870810, clinical response rates with RO6870810 were infrequent and of short duration when they occurred. This is in line with the preliminary activity of RO687081 observed in the first-in-human dose-escalation trial where ORRs were 25% (2/8), 2% (1/47), and 11% (2/19) for patients with nuclear protein of the testis carcinoma (NUT carcinoma), other solid tumors, and diffuse large B-cell lymphoma (DLBCL), respectively [ 9 ]. Limited clinical data exist on the use of other BET inhibitors in multiple myeloma.…”
supporting
confidence: 82%
“…While our pharmacodynamic findings provided evidence for on-target effects of RO6870810, clinical response rates with RO6870810 were infrequent and of short duration when they occurred. This is in line with the preliminary activity of RO687081 observed in the first-in-human dose-escalation trial where ORRs were 25% (2/8), 2% (1/47), and 11% (2/19) for patients with nuclear protein of the testis carcinoma (NUT carcinoma), other solid tumors, and diffuse large B-cell lymphoma (DLBCL), respectively [ 9 ]. Limited clinical data exist on the use of other BET inhibitors in multiple myeloma.…”
supporting
confidence: 82%
“…However, it outperforms JQ1 in solubility, metabolic stability, and binding to serotonin receptors. Additionally, alpha assay technology shows the remarkable affinity of RO6870810 toward the acetyl-lysine recognition pocket of the BET family [ 722 , 723 ].…”
Section: Myc Inhibitorsmentioning
confidence: 99%
“…A novel iBET RO6870810 (also known as RG6146 and TEN-0) can dissociate the BRD-NUT oncoproteins from DNA, inhibiting the proliferation of cancer cells. RO6870810 has also been tested on DLBCL where MYC is associated with the aggressiveness of DLBCL [ 722 ]. The clinical potential of RO6870810 is now being evaluated in clinical trials.…”
Section: Myc Inhibitorsmentioning
confidence: 99%
“…The role of BRD3 and BRD4 in cancer was first described in nuclear protein of testis (NUT) carcinoma, where a translocation causes BRD4 to fuse to NUT, driving cancer development [66,67]. It was then shown that BET inhibition can affect enhancer-driven oncogene expression in cancer cell lines [68] and one BET inhibitor passed Phase I in a clinical trial to treat NUT carcinoma (NCT01987362 i [69]). A study on prostate cancer found that selective inhibition of only the second bromodomain with ABBV-744 leads to fewer unwanted effects as compared with a pan-BET inhibitor, suggesting selective inhibition may be a valuable direction for treatment optimization [70].…”
Section: Trends In Molecular Medicinementioning
confidence: 99%